Functional Diversity of Thalamic Reticular Subnetworks - Crabtree, John W. (Frontiers in Systems Neuroscience, 2018)
The activity of the GABAergic neurons of the thalamic reticular nucleus (TRN) has long been known to play important roles in modulating the flow of information through the thalamus and in generating changes in thalamic activity during transitions from wakefulness to sleep. Recently, technological advances have considerably expanded our understanding of the functional organization of TRN. These have identified an impressive array of functionally distinct subnetworks in TRN that participate in sensory, motor, and/or cognitive processes through their differential functional connections with thalamic projection neurons operating as various types of relays. Accordingly, thalamic neurons acting as “first order” relays, which receive “driver” inputs from subcortical sources, are connected to a densely distributed TRN subnetwork composed of multiple elongated neural clusters that are topographically organized and incorporate spatially corresponding electrically connected neurons first order relays are also connected to TRN subnetworks exhibiting different state-dependent activity profiles. Thalamic neurons acting as “higher order” relays, which receive driver inputs from cortical layer 5, are connected to a densely distributed TRN subnetwork composed of multiple broad neural clusters that are non-topographically organized and incorporate spatially corresponding electrically connected neurons. And thalamic neurons acting as driver-like-recipient relays, which receive “driver-like” inputs from the superior colliculus or basal ganglia, are connected to TRN subnetworks composed of either elongated or broad neural clusters. Furthermore, TRN subnetworks that mediate interactions among neurons within groups of thalamic nuclei are connected to all three types of thalamic relays. In addition, several TRN subnetworks mediate various bottom-up, top-down, and internuclear attentional processes: some bottom-up and top-down attentional mechanisms are specifically related to first order thalamic relays whereas internuclear attentional mechanisms engage all three types of thalamic relays. The TRN subnetworks formed by elongated or broad neural clusters may act as templates to guide the operations of the TRN subnetworks related to attentional processes. In this review, the evidence revealing the functional TRN subnetworks will be evaluated and will be discussed in relation to the functions of the various sensory and motor thalamic nuclei with which these subnetworks are connected.